Resource utilization and costs of transitioning from pediatric to adult care for patients with chronic autoinflammatory and autoimmune disorders - Daniela Choukair; Christian Patry; Ronny Lehmann; Dorothea Treiber; Georg F. Hoffmann; Corinna Grasemann; Normi Bruck; Reinhard Berner; Peter Burgard; Hanns-Martin Lorenz; Burkhard Tönshoff (BMC, 2024)
Abstract Background A structured transition of adolescents and young adults with chronic autoinflammatory and autoimmune disorders from the pediatric to the adult health care system is important. To date, data on the time, processes, outcome, resources required for the necessary components of the transition process and the associated costs are lacking. Methods Evaluation of resource use and costs in a prospective cohort study of 58 adolescents with chronic autoinflammatory and autoimmune disorders, for the key elements of a structured transition pathway including (i) compilation of a summary of patient history, (ii) assessment of patients' disease-related knowledge and needs, (iii) required education and counseling sessions, (iv) and a transfer appointment of the patient with the current pediatric and the future adult rheumatologist. Results Forty-nine of 58 enrolled patients (84.5%) completed the transition pathway and were transferred to adult care. The mean time from the decision to start the transition process to the final transfer consultation was 315 ± 147 days. Transfer consultations were performed in 49 patients, including 10 patients jointly with the future adult rheumatologist. Most consultations were performed by the multidisciplinary team with a median of three team members and lasted 65.5 ± 21.3 min. The cumulative cost of all consultation and education sessions performed including the transfer appointment was 283 ± 164 Euro per patient. In addition, the cost of coordinating the transition process was 57.3 ± 15.4 Euro. Conclusions A structured transition pathway for patients with chronic autoinflammatory and autoimmune disorders is resource and time consuming and should be adequately funded.